Study of exclusive photoproduction of charmonium in ultra-peripheral lead-lead collisions - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Journal of high energy physics, 2023)
The cross-sections of exclusive (coherent) photoproduction J/ψ and ψ(2S) mesons in ultra-peripheral PbPb collisions at a nucleon-nucleon centre-of-mass energy of 5.02 TeV are measured using a data sample corresponding to an integrated luminosity of 228 ± 10 μb−1, collected by the LHCb experiment in 2018. The differential cross-sections are measured separately as a function of transverse momentum and rapidity in the nucleus-nucleus centre-of-mass frame for J/ψ and ψ(2S) mesons. The integrated cross-sections are measured to be σcoh J/ψ = 5.965 ± 0.059 ± 0.232 ± 0.262 mb and σcoh ψ(2S) = 0.923 ± 0.086 ± 0.028 ± 0.040 mb, where the first listed uncertainty is statistical, the second systematic and the third due to the luminosity determination. The cross-section ratio is measured to be σcoh ψ(2S)/σcoh J/ψ= 0.155 ± 0.014 ± 0.003, where the first uncertainty is statistical and the second is systematic. These results are compatible with theoretical predictions.
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, M. Bachmayer, D. Berninghoff, M. Borsato, R. Caspary, G. Frau, J. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, J. Kubat, B. Leverington, P. Li, J. Marks, D.J. Unverzagt, U. Uwer, L. Witola, A. Zhelezov [und viele weitere]
Gesehen am 20.10.2023